Response of rosemary plant to the effect of Nano-NPK fertilizer and biological factors and their effect on the active substances - Hamid H. Mahewish; Falah H. Radi; Mohammed N . Radhi (University of Thi-Qar Journal of agricultural research, 2021)
The study was carried out in the canopy-covered by Alsaran of the Faculty of Agriculture and marshes University of Thi- Qar on 01.11.2020. The experiment was terminated on 15.06.2021 On the rosemary plant that old of age was one year at three seedlings per unit experimental, thus became the number of seedlings 81 Seedlings in plastic anvils, container on sandy loam soil and peat moss with a percentage 3 :1 The experiment included the treatment of the balanced compound Nano-NPK fertilizer by spray on leaves of the plant at concentrations ( 0, 25, 75) mg. l-1 by three times for a period 15th day between one adding and another, and the biological factor was added at concentrations (0, 10, 20) ml by one adding. And carried out an experiment factorial according to Randomized Complete Block Design RCBD With three replications for each treatment, the results were compared according to the least significant difference test at the probability level of 5%. The statistical analysis results showed superiority in the compound Nano-fertilizer by height and number of branches, amount of oil and its density, and some of the active substances Cymen And the Camphene And Rose Mari acid reached (53.44 cm, 78.66 branches, 2.2989 g 00. gm-1, 1.0348, 4.671, 135.70) respectively compared to the lowest value for the comparison treatment. The biological factor was superior in the following characteristics (height, branches number, oil quantity, oil density, and active compounds). Cymen and the Camphene and Rose Mari acid reached (49.77 cm, 67.44) and 2.3277 g.100. g-1), respectively, compared with the lowest value for comparative treatment. As for the interaction, the treatment outperformed N2B2 In the adjective of the number of branches insignificant, and the treatment of N2B1 In the amount of oil, oil density and some active compounds, Rose Mari acid. It had a significant effect on the treatment N0B1 Significant effect on the active compound Camphene.